Repeated Takes: A Short History of Recording and its Effects on Music - Chanan, Michael (London Verso, 1995)
Michael Chanan considers the record as a radically new type of commodity which turned the intangible performance of music into a saleable object, and describes the upset which this caused in musical culture. He asks: What goes on in a recording studio? How does it affect the music? Do we listen to music differently because of reproduction?Repeated Takes relates the growth and development of the industry, both technically and economically; the effects of the microphone on interpretation in both classical and popular music; and the impact of all these factors on musical styles and taste. This highly readable book also traces the connections between the development of recording and the rise of new forms of popular music, and discusses arguments among classical musicians about microphone technique and studio practice.
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Technology; Sound recording industry; Music history; Cuckoo